MENGAPRESIASIKAN HASIL PRESTASI BELAJAR IPA PADA MATERI SISTEM GERAK MANUSIA MELALUI DISVERSITY OF STUDENT STRATEGY LEARNING SEBAGAI METODE PEMBELAJARAN SISWA KELAS VIII SMPN 1 SEKARAN - Suharno (FKIP, Universitas Billfath Lamongan, 2020)
This study aims to determine the results of natural science learning achievement in the human motion system by using the Diversity of Student Strategic Learning method (Learning Strategies that take account of student diversity). This research was included in a class action research that was designed into two cycles. Each cycle consists of planning, implementing, observing, and reflecting. Based on the results of research that has been done, the results obtained, namely the basic capabilities of the material motion system in humans can be achieved properly. This can be seen in the results of student evaluations that reach 78.25% completeness. The data is used as a basis for designing cycle 1, so as to obtain the results of the activities of students who have good activities in learning activities as many as 17 (68%) and as many as 4 (16%) and as many as 4 (16%) indicate less activity. While observations from the point of view of students' attention in learning activities, students who have good attention are 9 (36%), who have attention as much as 6 (24%) and less attention is 10 (40%). The use of the Diversity of Student Strategic Learning method can increase the activities and attention of students in Biology / Natural Sciences lessons yet to be declared Completed. then the research activities need to be held in the second cycle, so that the results obtained by students who have good activities in learning activities as many as 21 (84%) and as many as 2 (8%) and as many as 2 (8%) indicate less activity. While observations from the point of view of students 'attention in learning activities, students who have good attention are 19 (76%), parents' attention are 4 (16%) and attention is less 2 (8%). So, it can be concluded that the Diversity of Student Strategic Learning method (Learning Strategies that considers student diversity) can increase student activities and attention in Biology / Natural Sciences. By using the Diversity of Student Strategic Learning method.